“We just have to help”: Community health workers' informal task-shifting and task-sharing practices for hypertension and diabetes care in Nigeria - Ajisegiri, Whenayon Simeon; Abimbola, Seye; Tesema, Azeb Gebresilassie; Odusanya, Olumuyiwa O.; Peiris, David; Joshi, Rohina (Frontiers in Public Health, 2023)
Nigeria’s skilled health professional health workforce density is insufficient to achieve its national targets for non-communicable diseases (NCD) which include 25% reduction in the prevalence of diabetes and hypertension, particularly at the primary health care (PHC) level. This places a great demand on community health workers (CHWs) who constitute the majority of PHC workers. Traditionally, CHWs are mainly involved in infectious diseases programmes, and maternal and child health services. Their involvement with prevention and control of NCDs has been minimal. With government prioritization of PHC for combating the rising NCD burden, strengthening CHWs’ skills and competencies for NCD care delivery is crucial. We conducted a mixed methods study to explore the roles and practices of CHWs in the delivery of hypertension and diabetes care at PHC facilities in four states (two each in northern and southern regions) in Nigeria. We reviewed the National Standing Orders that guide CHWs’ practices at the PHC facilities and administered a survey to 76 CHWs and conducted 13 focus groups (90 participants), and in-depth individual interviews with 13 CHWs and 7 other local and state government stakeholders. Overall, we found that despite capacity constraints, CHWs frequently delivered services beyond the scope of practice stipulated in the National Standing Orders. Such informal task-shifting practices were primarily motivated by a need to serve the community. While these practices may partially support health system functions and address unmet need, they may also lead to variable care quality and safety. Several factors could mitigate these adverse impacts and strengthen CHW roles in the health system. These include a stronger enabling policy environment to support NCD task-sharing, investment in continuous capacity building for CHWs, improved guidelines that can be implemented at the point of care, and improved coordination processes between PHC and higher-level facilities.